An investigation into idiomatic expressions containing numbers in English and Vietnamese. M.A Thesis Linguistics: 60 22 15 - Nguyễn, Thị Thủy Tiên (ĐHNN, 2017)
Idioms have been a linguistic matter attracting a lot of attention of linguistic researchers and English learners. They are often used in life such as daily conversations and literature works. Idioms are concerned with a large number of matters in life. Wi (...)